MiR-208b Regulates the Conversion of Skeletal Muscle Fiber Types by Inhibiting Mettl8 Expression - Li, Xiang; Bi, Hanfang; Xie, Shanshan; Cui, Wentao (Frontiers in Genetics, 2022)
Skeletal muscle, the main source of animal meat products, contains muscle fiber as a key unit. It is well known that transformation takes place between different types of muscle fibers, however, the conversion mechanism is not clear. In a previous study, our lab has demonstrated that there is a decrease in type I muscle fibers and an increase in type IIB muscle fibers in skeletal muscle of myostatin gene-edited Meishan pigs. Very interestingly, we observed the down regulation of miR-208b expression and an increase in expression the predicted target gene Mettl8 (Methyltransferase like 8) in skeletal muscle of MSTN gene-edited Meishan pigs. These results reveal that there is a potential connection between the conversion of skeletal muscle fiber types and miR-208b and Mettl8 expression. In this study, we first explored the expression patterns of miR-208b and Mettl8 in skeletal muscle in Meishan pigs; and then C2C12 cells were used to simulate the development and maturation of muscle fibers. Our results indicated that Myh4 expression level decreased and Myh7 expression level increased following overexpression of miR-208b in C2C12 cells. We therefore speculate that that miR-208b can promote the conversion of fast-twitch fibers to slow-twitch fibers. The targeting relationship between Mettl8 and miR-208b was confirmed by results obtained using dual luciferase assay, RT-qPCR, and WB analysis. Following the transfection of Mettl8 siRNA into C2C12 cells, we observed that Mettl8 expression decreased significantly while Myh7 expression increased and Myh4 expression decreased, indicating that Mettl8 promotes the conversion of slow muscle fibers to fast muscle fibers. Additionally, changes in skeletal muscle fiber types are observed in those mice where miR-208b and Mettl8 genes are knocked out. The miR-208b knockout promotes the formation of slow muscle fibers, and the Mettl8 knockout promotes the formation of fast muscle fibers. In conclusion, our research results show that miR-208b regulates the conversion of different muscle fiber types by inhibiting Mettl8 expression.